Efforts Made by the Government and Companies in Overcoming the Impact of Covid-19 for Workers - Tri Reni Novita (IHSA Institute, 2022)
The company took various alternative steps to avoid layoffs due to Covid-19, including reducing wages and facilities for top-level workers (eg manager, director level); reduce work shifts; reduce working hours; reduce working days; and lay off or lay off workers/ laborers in rotation for a while. Then do not extend the contract for workers whose contract period has expired and provide pensions for those who have met the requirements. The development and improvement of the competency quality of Human Resources (HR) is pursued through reforms in the education sector so that it can reach all levels of society. It is very important for academics to carry out educational reforms in the form of synchronization from the demand and supply sides in vocational training for the workforce, so that vocational institutions can flexibly adapt to the dynamics of work in the current industrial 4.0 era. A number of strategies in education reform have been carried out. Among them are curriculum renewal, study program development and the construction of research and innovation centers aimed at improving the quality of human resources.